Influencia del vinculo familiar en el rendimiento escolar de las alumnas de la institución educativa primaria n° 80397 "hermanos albujar y manuel guarniz" del distrito de guadalupe. - Vilca Acuña, Ronal Abel (2013)
This research was studied the “INFLUENCE OF LINK FAMILY SCHOOL PERFORMANCE”, research was conducted in the Educational Institution PrimaryNº. 80397 “BROTHERS ALBUJAR AND MANUEL GUARNIZ”, the sample with cualse intervened was 222 participants. Utilizadafueron interview techniques, questionnaire, group discussion and participant observation, associated with critical pedagogy Freire reflective dialogue based. Therefore aims to raise awareness of the influence of family ties in school performance, and is embodied in the following way. CHAPTER I: Framework addresses the link variables Teóricocon parents - daughters where the word family is conceptualized. CHAPTER II: This raises the second variable, problem formulation, hypothesis, objectives and the sample which intervened. CHAPTER III: We present the analysis and interpretation of the results presentation from the information gathered during the development of research through questionnaires administered to student’s elementary student. CHAPTER IV: Response data analysis and yielded the same results, with a discussion of results. CHAPTER V: Finally it shows the conclusions and recommendations of this work, bibliography and relevant annexes.